Personality correlates of job stress and organisational citizenship behaviour among hospital professionals - Kaul, Tushar; Srivastava, Rani; Sabharwal, Manish; Jha, Priyanka; Debapriya (International Journal of Research in Medical Sciences, 2025)
Background: Understanding the role of personality in occupational stress and organisational citizenship behaviour (OCB) is crucial in healthcare environments, where professionals often face high-pressure situations. In Indian healthcare settings, research on how personality dimensions impact stress levels and prosocial workplace behaviours remains limited. Aim was to examine the correlation between big five personality dimensions (extraversion, agreeableness, conscientiousness, openness and neuroticism), occupational stress, and OCB among hospital professionals. Methods: A cross-sectional study was conducted among 254 full-time employees from Santosh Hospital in Ghaziabad, Uttar Pradesh, India using purposive sampling. Participants included doctors, nurses, technical, and non-technical (administrative) staff. Standardized tools- the big five inventory (BFI), occupational stress index (OSI), general health questionnaire (GHQ-12), and organisational citizenship behaviour checklist (OCB-C)- were administered as physical forms. Descriptive statistics and inferential statistics (Pearson correlation) were performed. Results: Neuroticism was positively correlated with occupational stress (r=0.201**) and negatively with OCB (r=–0.170**), indicating a dual relationship. OCB was significantly associated with extraversion (r=0.142*), agreeableness (r=0.187**), and conscientiousness (r=0.145*). Psychological distress (GHQ scores) correlated negatively with extraversion, agreeableness, conscientiousness, and openness. The mean OCB score was 64.24 (SD±12.51), suggesting moderate prosocial workplace behaviour (* = p<0.05, ** = p<0.01). Conclusions: Personality dimensions significantly influence both job stress and OCB. These findings underscore the importance of personality in healthcare context, specifically Indian healthcare scenario among doctors, nurses, technical and non-technical/administrative staff.